The other side of 9/11- Obstacles and challenges facing SADC countries in implementing UN Security Council resolution 1373 (2001) relating to terrorism. - Seyuba, Mishinga (Department of Commercial Law, 2024)
This dissertation analyses the major obstacles and challenges that SADC countries are facing in the context of implementing UN Security Council Resolution 1373 relating to terrorism. It sets out to evaluate how successful efforts to strengthen legal and institutional mechanisms within SADC to combat terrorism have been. The dissertation will assess the impact that terrorism has on governance, legal, economic and political issues primarily within SADC and Kenya. What are the direct and indirect implications of Resolution 1373? Who has implemented and who has not? What have some of the problems, obstacles and challenges been in submitting CTC reports? How much international assistance and support is currently being given to member states of the SADC? What is the rate of international support? Answers to these questions will be based upon a research analysis. The main obstacle that SADC countries are facing regarding Resolution 1373 is the problems of inadequate resources to deal with terrorism coupled with capacity problems. The paper will argue why this is so.